Kinematic Analysis and MATLAB Applications of 2-3RRR Mechanism Chain (Journal of Informatics and Mathematical Sciences, 2020)
The Stewart platform is a mechanism design based on movement of two planes relative to each other by the motion of links. These type of mechanism can be structurally designed in many different ways. In this paper, the joints of connection points of fixed platform to moving platform is determined as RRR with three legs. A software has been developed in the MATLAB environment, which makes calculations using this Stewart platfom mechanism's transformation matrix by applying Denavit Hartenberg convention.
Keywords: Denavit-Hartenberg representation; mechanism chain; Stewart platform